American Literature I An Anthology of Texts From Early America Through the Civil War - Kurtz, Jenifer (Open textbook library., 2020)
This book offers an anthology of texts that includes letters, journals, poetry, newspaper articles, pamphlets, sermons, narratives, and short fiction written in and about America beginning with collected oral stories from Native American tribes and ending with the poetry of Emily Dickinson. Many major and minor authors are included, providing a sampling of the different styles, topics, cultures, and concerns present during the formation and development of America through the mid-nineteenth century.